Rafflesia parvimaculata (Rafflesiaceae), a new species of Rafflesia from Peninsular Malaysia - Sofiyanti, Nery; Mat-Salleh, Kamarudin; Mahmud, Khairil; Mazlan, Nor Zuhailah; Hasein, Mohd. Ros. Albukharey; Burslem, David F.r.p. (Phytotaxa, 2016)
The new species Rafflesia parvimaculata is described from Pahang, Peninsular Malaysia. This species is characterized by its numerous small white warts on the perigone lobes, and also by its slender, unbranched, capitate ramenta that are white in color and densely arranged inside the floral perigone tube. These unique characters distinguish R. parvimaculata from other Rafflesia species. The discovery of this new species brings the total number of Rafflesia species described from Peninsular Malaysia to five